TATTOO PIGMENT IN SENTINEL LYMPH NODE OF PRIMARY BREAST CANCER PATIENT. (February 2015) - Jayaratne, Prasad; Wright, Gordon; Day, Christopher; Manley, Russell
Abstract : Case report of observation not previously described. Pigment from tattoos is known to accumulate in regional lymph nodes. The location of tattoos may be close to a tumour. The presence of pigment from tattoos may distort the morphology of sentinel lymph nodes. It is not known whether there is drainage of pigment from tattoos selectively to regional sentinel lymph node. We report a case in which metastatic cells from a primary left breast carcinoma were found in a sentinel lymph node which also demonstrated pigment from a skin tattoo located close to the site of the breast tumour. Subsequent lymphadenectomy from the left axilla showed 21 additional lymph nodes with neither metastatic carcinoma nor pigment accumulation. This supports the hypothesis of preferential drainage of pigment from skin to sentinel nodes in the region in question. This may be important in considering the management of patients with a primary tumour close to the location of a tattoo.